Fidelização de clientes a livrarias virtuais: um modelo heurístico - Rodrigues, Elaine Maria Tavares (2002)
The conventional commercial relationship between suppliers and customers has undergone a profound change as a result of the technological advances that have been made in electronic transactions, such as the Internet. These transformations have not been entirely technological in nature, as they have also directly altered marketing activities. Due to a series of factors, companies are increasingly driven by their customer wishes and requirements, with Electronic Commerce being just one of the means of developing and maintaining this type of relationship, called Customer Relations Marketing. The Internet sites available allow companies to obtain information more easily about which aspects are most relevant to their target customer group in terms of their products and services, helping them to increase the value of commercial transactions on offer. The online marketing strategies of electronic retail companies aim to cultivate customer loyalty after the first purchase has been made, so that customers make repeat purchases. Virtual bookstores represent a particularly successful sector in the world of Electronic Commerce. However, to ensure profitability, the business models of these companies need to be based on customer loyalty, as there is stiff competition in this area. This research study seeks to develop a heuristic model, called 4Ps and 1F, for customer loyalty to virtual bookstores. The 4Ps represent one of the most traditional marketing concepts and the F relates to Customer Loyalty. In developing this model the aim is to see how each marketing P influences customer loyalty, thus identifying the factors critical to the success of virtual bookstores retaining customer loyalty.